How Teacher and Peer Environments Influence Student Well-Being through Religiosity in an Islamic Boarding School - Nurul Latifatul Inayati; Mutahharun Jinan; Istanto; Ajeng Nova Dumpratiwi; Muhammad Zidan Nur Ihsan; Talitha Javier; Ma’ruf Alfattah (Edudeena : Journal of Islamic Religious Education, 2026)
This study aims to examine the direct and indirect influence of teachers' social support and peer environment on student well-being, with religiosity as a mediating variable. A quantitative approach was used using survey data collected from students in Islamic boarding schools, and the data was analyzed using structural equation modeling. The results show different patterns of influence. Teachers' social support has no significant direct influence on student well-being but operates entirely through religiosity, suggesting a full mediation mechanism. In contrast, the peer environment exerts direct and indirect influence, showing partial mediation through religiosity. Furthermore, religiosity shows a significant direct influence on student well-being, highlighting its central role as an internal psychological resource. These findings suggest that student well-being is not directly determined by external social factors but is largely shaped through the internalization of values. This study contributes to the literature by proposing an integrative model that emphasizes religiosity as a key psychological mechanism linking social contexts and well-being, particularly in the context of dormitory-based education